2006
DOI: 10.1002/jsfa.2744
|View full text |Cite
|
Sign up to set email alerts
|

In vitrostudy on antioxidant activities of peanut protein hydrolysate

Abstract: Peanut protein was hydrolysed with a commercial protease, Alcalase 2.4L, and the resulting hydrolysate was investigated for its antioxidant activities, including the ability to inhibit the autoxidation of linoleic acid, the scavenging effect on the 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical, the reducing power and the inhibition of liver lipid oxidation. As compared with the peanut protein, peanut protein hydrolysate showed strong inhibition of the autoxidation of linoleic acid, to scavenge DPPH free ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…As shown in Fig. 7A-C, the level of linoleic acid peroxides in the control, with no added leaf extract fractions increased rapidly and reached the highest peak by the fourth day followed by a decline as the incubation time increased; this was in accordance with previous observations (Jayaprakasha et al, 2001;Chen, Zhao, Cong, & Bao, 2007;Pownall et al, 2010). The authors reported that the rapid decline in absorbance of the control is due to the decomposition of (hydro) peroxides as the incubation time was increased.…”
Section: Inhibition Of Linoleic Acid Oxidationsupporting
confidence: 89%
“…As shown in Fig. 7A-C, the level of linoleic acid peroxides in the control, with no added leaf extract fractions increased rapidly and reached the highest peak by the fourth day followed by a decline as the incubation time increased; this was in accordance with previous observations (Jayaprakasha et al, 2001;Chen, Zhao, Cong, & Bao, 2007;Pownall et al, 2010). The authors reported that the rapid decline in absorbance of the control is due to the decomposition of (hydro) peroxides as the incubation time was increased.…”
Section: Inhibition Of Linoleic Acid Oxidationsupporting
confidence: 89%
“…3, SUGHs-I prepared with all four proteases were found to have the ability of scavenging DPPH radical in a dosedependent manner at the concentration of 1.25e10 mg/mL (protein basis). The scavenging effects of the four SUGHs-Is were significantly lower than that of Vit-C (P < 0.05) but close to or stronger than that of other protein hydrolysates (Chen, Zhao, Zhao, Cong, & Bao, 2007;Wang, Zhu, Han, & Wang, 2008;Yang, Ho, Chu, & Chow, 2008). Five milligrams per milliliter (protein basis) of SUGHs-I prepared with neutral protease, papain, trypsin, and pepsin exhibited 62.80%, 53.13%, 52.11%, and 43.11% of scavenging percentage, respectively.…”
Section: Antioxidant Activitymentioning
confidence: 70%
“…Although, they are less effective than synthetic antioxidants (Sarmadi & Ismail, 2010), natural antioxidants such as antioxidant peptides have received more attraction due to having safer and milder activity. These peptides have been isolated from various protein sources, such as potato (Kudo, Onodera, Takeda, Benkeblia, & Shiomi, 2009), rice endosperm (Zhang et al, 2010), peanut (Chen, Zhao, Zhao, Cong, & Bao, 2007), soy (Moure, Dominguez, & Parajo, 2005), corn gluten (Li, Han, & Chen, 2008), and sunflower (Vioque et al, 2008). The presence and proper position of basic or/and acidic, aromatic and hydrophobic amino acid residues within peptide sequence can lead to enhance the antioxidant activities (Chen, Muramoto, Yamauchi, Fujimoto, & Nokihara, 1998).…”
Section: Introductionmentioning
confidence: 98%